Tracer uptake in mediastinal and paraaortal thoracic lymph nodes as a potential pitfall in image interpretation of PSMA ligand PET/CT - Afshar-Oromieh, Ali; Holland-Letz, Tim; Mier, Walter; Kiß, Oliver; Kopka, Klaus; Haberkorn, Uwe; Sattler, Lars Peter; Weichert, Wilko (European journal of nuclear medicine and molecular imaging, 2018)
PurposeSince the introduction of 68Ga-PSMA-11 PET/CT for imaging prostate cancer (PC) we have frequently observed mediastinal lymph nodes (LN) showing tracer uptake despite being classified as benign. The aim of this evaluation was to further analyze such LN.MethodsTwo patient groups with biphasic 68Ga-PSMA-11 PET/CT at 1 h and 3 h p.i. were included in this retrospective evaluation. Group A (n = 38) included patients without LN metastases, and group B (n = 43) patients with LN metastases of PC. SUV of mediastinal/paraaortal LN of group A (n = 100) were compared to SUV of LN metastases of group B (n = 91). Additionally, 22 randomly selected mediastinal and paraaortal LN of patients without PC were immunohistochemically (IHC) analyzed for PSMA expression.ResultsIn group A, 7/38 patients (18.4%) presented with at least one PSMA-positive mediastinal LN at 1 h p.i. and 3/38 (7.9%) positive LN at 3 h p.i. with a SUVmax of 2.3 ± 0.7 at 1 h p.i. (2.0 ± 0.7 at 3 h p.i.). A total of 11 PSMA-positive mediastinal/paraaortal LN were detected in nine patients considering both imaging timing points. SUVmax of LN-metastases was 12.5 ± 13.2 at 1 h p.i. (15.8 ± 17.0 at 3 h p.i.). SUVmax increased clearly (> 10%) between 1 h and 3 h p.i. in 76.9% of the LN metastases, and decreased significantly in 72.7% of the mediastinal/paraaortal LN. By IHC, PSMA-expression was observed in intranodal vascular endothelia of all investigated LN groups and to differing degrees within germinal centers of 15/22 of them (68.1%). Expression was stronger in mediastinal nodes (p = 0.038) and when follicular hyperplasia was present (p = 0.050).ConclusionPSMA-positive mediastinal/paraaortal benign LN were visible in a notable proportion of patients. PSMA-positivity on the histopathological level was associated with the activation state of the LN. However, in contrast to LN metastases of PC, they presented with significantly lower uptake, which, in addition, usually decreased over time.
Gesehen am 10.05.2019